UNVEILING THE PROBLEM-SOLVING APTITUDE: A COMPARATIVE EXPLORATION OF EXPERIENCED TEACHERS AND STUDENT-TEACHERS - Gururaja, C.S; Thirumalesha; Sangtam, T. Yolila; Christopher, T Arun (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This study explores the problem-solving aptitude of experienced teachers and student-teachers, emphasizing its significance in effective teaching and learning. Grounded in Cognitive Load, Experiential Learning, and Social Learning theories, the research delves into how these frameworks shape problem-solving skills across different teaching experience levels. Through a comparative analysis, the study investigates preferences for problem-solving tactics—such as collaboration, compliance, and adaptability—among these two groups. A mixed-methods approach was employed, utilizing situational judgment scales and pre-test and post-test designs with 422 participants, including experienced teachers and student-teachers from two years B.Ed. Program. Key findings reveal nuanced differences in how these groups approach challenges. While experienced teachers demonstrate a greater tendency for collaborative and consultative methods, student-teachers exhibit growing adaptability as they progress through training programs. Both groups consistently avoid counterproductive tactics like retaliation or evasion. The study highlights the interplay between theoretical knowledge and practical application, showcasing the importance of mentorship and reflective practice in fostering problem-solving capabilities among student-teachers. The implications are significant for teacher education programs, suggesting the integration of experiential and theoretical learning to cultivate critical problem-solving skills. The research underscores the necessity for a holistic approach to teacher development, bridging the gap between novice and expert educators to enhance overall teaching efficacy and adaptability in dynamic educational environments.